ANALYSIS OF STUDENTS' ERRORS OF CLASS XI SMKN 2 PALU IN SOLVING MATRIX STORY PROBLEMS USING NEWMAN - Ermayanti, Ni Luh; Sugita, Gandung; Alfisyahra, Alfisyahra; Murdiana, I Nyoman (Universitas Sembilanbelas November Kolaka, 2024)
The purpose of this study was to obtain a description of the mistakes made by class XI students of SMK Negeri 2 Palu in solving word problems on matrix material based on Newman's stages. The type of research used is qualitative research. The research design consists of planning, implementation and completion stages. The research subjects were 3 students of class XI at SMK Negeri 2 Palu. The results of this study indicate that DE subjects experienced errors at the stages of understanding the problem, the stage of transformation, the stage of processing skills, and the stage of writing the final answer. The HR subject experienced errors at the stage of transformation, stage of process skills and stage of writing the final answer. The RW subject experienced errors at the stages of understanding the problem, the transformation stage, the process skills stage, and the final answer writing stage. Therefore, it was concluded that all subjects did not experience errors in the question reading stage. Tujuan penelitian ini adalah untuk memperoleh deskripsi mengenai kesalahan siswa kelas XI SMK Negeri 2 Palu dalam menyelesaikan soal cerita pada materi matriks berdasarkan tahapan Newman. Jenis penelitian yang digunakan adalah penelitian kualitatif. Desain penelitian terdiri dari tahapan perencanaan, pelaksanaan dan penyelesaian. Subjek penelitian adalah 3 orang siswa kelas XI SMK Negeri 2 Palu dengan beberapa pertimbangan yaitu; siswa paling banyak melakukan kesalahan, memiliki kesalahan berbeda, kesalahan dapat mewakili kesalahan yang dilakukan oleh siswa lain, siswa tersebut mempunyai kemampuan komunikasi yang baik, kesedian siswa menjadi subjek, dan rekomendasi guru matematika SMK Negeri 2 Palu. Hasil penelitian ini menunjukkan bahwa subjek DE tidak mengalami kesalahan pada tahap membaca soal, akan tetapi subjek mengalami kesalahan pada tahap memahami masalah, tahap transformasi, tahap keterampilan proses, dan tahap penulisan jawaban akhir. Subjek HR tidak mengalami kesalahan pada tahap membaca soal dan tahap memahami masalah, akan tetapi subjek mengalami kesalahan pada tahap transformasi, tahap keterampilan proses, dan tahap penulisan jawaban akhir. Subjek RW tidak mengalami kesalahan pada tahap membaca soal, akan tetapi subjek mengalami kesalahan pada tahap memahami masalah, tahap transformasi, tahap keterampilan proses, dan tahap penulisan jawaban akhir.The purpose of this study was to obtain a description of the mistakes made by class XI students of SMK Negeri 2 Palu in solving word problems on matrix material based on Newman's stages. The type of research used is qualitative research. The research design consists of planning, implementation and completion stages. The research subjects were 3 students of class XI at SMK Negeri 2 Palu with several considerations namely; students make the most mistakes, have different mistakes, mistakes can represent mistakes made by other students, these students have good communication skills, the willingness of students to become subjects, and recommendations for mathematics teachers at SMK Negeri 2 Palu. The results of this study indicate that DE subjects did not experience errors at the stage of reading the questions, but subjects experienced errors at the stages of understanding the problem, the stage of transformation, the stage of processing skills, and the stage of writing the final answer. The HR subject did not experience errors at the stage of reading the questions and the stage of understanding the problem, but the subject experienced errors at the stage of transformation, stage of process skills and stage of writing the final answer. The RW subject did not experience errors at the stage of reading the questions, but the subject experienced errors at the stages of understanding the problem, the transformation stage, the process skills stage, and the final answer writing stage.